2014
DOI: 10.1007/s00381-014-2510-8
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of desflurane versus propofol on transcranial motor-evoked potentials in pediatric patients

Abstract: MEPs with good amplitudes were obtained under desflurane only anesthesia that were comparable to propofol only anesthesia in pediatric patients during surgery for spinal deformities. There was no evidence for anesthetic fade over the time period examined. When used by itself, desflurane can be considered a viable alternative to propofol anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 21 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…The observed effect appears to be more pronounced in myelopathic than neurologically normal patients, but the underlying mechanism responsible remains unclear. In contrast, Holdefer et al [ 7 ] reviewed MEP amplitudes of 50 patients receiving desflurane or propofol during spinal deformity surgery but found no evidence of reducing trend with time. This was corroborated by a separate study [ 8 ] which also found no significant MEP amplitude changes over 120 min during propofol anesthesia for spinal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The observed effect appears to be more pronounced in myelopathic than neurologically normal patients, but the underlying mechanism responsible remains unclear. In contrast, Holdefer et al [ 7 ] reviewed MEP amplitudes of 50 patients receiving desflurane or propofol during spinal deformity surgery but found no evidence of reducing trend with time. This was corroborated by a separate study [ 8 ] which also found no significant MEP amplitude changes over 120 min during propofol anesthesia for spinal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Technical details of tcMEPs in children such as the optimal number of pulses during spine surgeries have been studied . The interactions between MEPs and various anesthetic agents have been studied, and MEPs are preserved in children who are administered either propofol or desflurane . In contrast, dexmedetomidine tends to attenuate tcMEP signals …”
Section: Resultsmentioning
confidence: 99%
“…We first determined if the anesthetic type altered evoked pressure (P det ) since some prior studies suggest that isoflurane may reduce sensory or motor evoked potentials [24, 25] and that propofol may reduce motor evoked potentials [26]. Five animals with intact bladder innervation were tested using isoflurane, and then propofol.…”
Section: Resultsmentioning
confidence: 99%